Impact on bird fauna of a non-native oyster expanding into blue mussel beds in the Dutch Wadden Sea. (October 2016) - Waser, Andreas M.; Deuzeman, Symen; Kangeri, Arno K. wa; van Winden, Erik; Postma, Jelle; de Boer, Peter; van der Meer, Jaap; Ens, Bruno J.
Abstract: Intertidal mussel beds are important for intertidal ecosystems, because they feature a high taxonomic diversity and abundance of benthic organisms and are important foraging grounds for many avian species. After the introduction of the Pacific oyster ( Crassostrea gigas ) into the European Wadden Sea, many mussel beds developed into oyster dominated bivalve beds. Despite the fact that oysters have been colonizing many European intertidal areas for about two decades, their impact on the ecosystem is still poorly understood. Here, we investigated the impact of oysters on the condition of mussels and on the spatial distribution of birds on 18 bivalve beds with different grades of oyster occurrence throughout the Dutch Wadden Sea. Moreover, in comparing bird densities on bivalve beds with densities expected on the total intertidal area, we could detect which species exhibit a preference for the structured habitat. Overall, 50 different bird species were observed on the beds, of which about half regularly frequent intertidal flats. Most of these species showed a preference for bivalve beds. The condition of mussels decreased with the oyster dominance, whereas the majority of bird species was not affected by the oyster occurrence. However, three of the four species that were negatively affected depend on intertidal mussels as food source. Even though the Pacific oyster is a nonnative species, attempts to fight it may do more harm to avian biodiversity than good. Graphical asbtract: Highlights: Half of the epibenthic bivalve beds in the Dutch Wadden Sea are a mix of Pacific oysters and native blue mussels. Most bird species prefer bivalve beds over bare intertidal flats. 20 out of 24 of the bird species were not affected by the Pacific oyster occurrence. Oysters negatively affected Common Gull, Dunlin, Oystercatcher, and Red Knot. Removal of the Pacific oyster will not aid the avian community.